An(other) truth: a feminist perspective on KPMG's true value. Issue 4 (7th November 2016) - Cooper, Christine; Senkl, Daniela
Abstract : Purpose: Through a feminist lens, this study aims to provide insight into the ability of KPMG's true value approach to include "the other" in the corporate value creation process and into its potential to introduce a more "multiple" form of accounting. Additionally, this study seeks to set up the true value approach within its broader social, economic and political context. Design/methodology/approach: The study uses an interpretative analysis of KPMG's document "A New Vision of Value; Connecting corporate and societal value creation". Findings: The KPMG document uses a language of fear of an external threat to promote its true value approach. It is suggested in this study that the concern of the KPMG approach is to include "the other" in their valuation model if it has an impact on corporate earnings. However, stakeholder actions or governmental regulations could be problematically attenuat by the document's use of a language which suggests integration of "the other" and which might be perceived as socially progressive. It is argue that the increase in societal or environmental value set out in the KPMG document depends upon "excessive" commodity production which uses up scarce environmental resources. Research limitations/implications: The implication of this research is that the daunting problems of inequality and environmental destruction cannot be solved by initiatives such as the KMPG true value technology. Practical implications: The paper argues that a feminine management or reporting framework would not need to fulfil the aim of managing the other in the sense of measurement and control, as it is not based on the fear of loss. It would instead be an approach of giving and caring. A feminine alternative, however, is difficult to express in phallogo-centric language. The ability to bring about change requires the capacity to understand the prevalent symbolic order and the willingness to challenge it. Social implications: The feminist perspective used in this paper to critically reflect on KPMG's true value approach and the neo-liberal economy in which it is embedded aims to create public awareness of the prevalent phallocentric symbolic order. Recognising the invisible power of the symbolic order is essential to be able to see how the new "integrative" management and reporting approaches are only slight modifications of the existing management and reporting tools. The paper highlights that these "alternatives" create the impression that business is dealing with the greatest global threats and can potentially be used to silence critics. Originality/value: This paper contributes to existing critiques of integrated or shared value approaches by taking a feminist view. Even though corporate claims of "win-win situations" (in which environmental degradation and inequality can be solved as business opportunities) have been critiqued in the literature, this study adopts a rather unusual perspective (in accounting). This approach argues that initiatives grounded in the phallogo-centric symbolic order are incapable of overcoming the current problems of our society; but they bear the risk of making the situation worse by creating a public impression that "someone is dealing appropriately with serious social and environmental issues".